Facilities of Female Handball Volitional Training - Meidus, Leonas (Acta Paedagogica Vilnensia, 2005)
High achievements in sports require not only good physical preparedness from the playres, but also certain moral features of their will. Specific psychological features that could be attributed are as follows: high movement activity, intense physical loads, concentrated attention, and constantly changing game situations, which relate to intense efforts of the players' will. Therefore, forming o f the features related to will become s one of the basic tasks for coaches. Successful development of such characteristics cannot be proceeded spontaneously, as it must be purposeful and fulfil certain conditions. T he aim of the present research is to determine the most important features of female handball players' will and to present a psychological analysis related to forming such skills. T he following methods were used during the research: literary resourse analysis, game activity observation, interviewing coache s and mathematical statistics. T he following basic female handball player will features were distinguished during the experiment: determination, persistence, self-control, initiative, and diligence. The participanting players were divided into two groups: A - playres having good physical and technical preparendness, and b - players whos e physical and technical preparedness wa s insufficient. A s analysis of the experimental results and a com parison of manifestation of the said will characteris tics between the two groups indicates that will-rela ted chracteristcs are expressed among female handball palyers to different degrees. The A-group players' determination, persistence, self-control, initiati vc, and diligence were , respectivity, equal to 67.0%, 59.0%, 19.0%, 20.0%, and 65.0%. Meanwhile , these parameters had much lower experessions in group B: 41.0%, 40.0%, %, 15.0%, 55.0%. T he results obtained allow drawing a conclusion that the degree to which female handball team players' will characteristics are expressed is directly connected with their physical and technical preparedness. Keywords: physical preparedness, technical preparedness, will-related efforts, determination, persistence, self-control, initiative, diligence.
Keywords: physical preparedness; technical preparedness; will-related efforts; determination; persistence; self-control; initiative; diligence